2021
DOI: 10.1177/13623613211062776
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in autism during unpredictable shifts of socio-emotional stimuli: Investigation of group and sex differences

Abstract: Considering the mixed nature of reports of flexibility difficulties in autism, we hypothesized that a task that more closely resembles the challenges faced in real life would help to assess these difficulties. Autistic and typically developing adults performed an online Emotional Shifting Task, involving non-explicit unpredictable shifts of complex socio-emotional stimuli, and the Task Switching Task, involving explicit predictable shifts of simple character stimuli. Switch cost (i.e. the difference in perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 109 publications
(158 reference statements)
2
6
0
Order By: Relevance
“…To extend previous works, our aim was to investigate a shift or change in emotional perception triggered by the context that occurs automatically and without explicit instructions to change. We used the Emotional Shifting Task (EST) [22,23], in which pairs of pictures are presented: the first one is a small detail of the second picture, as depicted in Fig 1 . The presentation of the first picture, which is a decontextualized part of the whole picture, generates an emotional response, but when this picture is put into a context, the context itself may cause a change (and in some cases a shift) in the meaning and valence of the stimulus. For instance, a picture of a smiling girl is generally evaluated as a positive stimulus but if it turns out that she is smiling while bullying a peer, it will probably cause a shift in the evaluation toward a negative direction automatically and without any explicit regulatory goals.…”
Section: Introductionmentioning
confidence: 99%
“…To extend previous works, our aim was to investigate a shift or change in emotional perception triggered by the context that occurs automatically and without explicit instructions to change. We used the Emotional Shifting Task (EST) [22,23], in which pairs of pictures are presented: the first one is a small detail of the second picture, as depicted in Fig 1 . The presentation of the first picture, which is a decontextualized part of the whole picture, generates an emotional response, but when this picture is put into a context, the context itself may cause a change (and in some cases a shift) in the meaning and valence of the stimulus. For instance, a picture of a smiling girl is generally evaluated as a positive stimulus but if it turns out that she is smiling while bullying a peer, it will probably cause a shift in the evaluation toward a negative direction automatically and without any explicit regulatory goals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the present study seeks to replicate and extend the ndings of Lacroix et al (2022). Indeed, Lacroix et al (2022) demonstrated increased di culty among autistic individuals, compared to nonautistic, in adjusting their predictions to the context of socio-emotional stimuli on the Emotional Flexibility task (EST), but it remains unclear if this effect is speci c to social stimuli or extends to all emotional stimuli.…”
Section: Introductionmentioning
confidence: 86%
“…Thus, the present study seeks to replicate and extend the ndings of Lacroix et al (2022). Indeed, Lacroix et al (2022) demonstrated increased di culty among autistic individuals, compared to nonautistic, in adjusting their predictions to the context of socio-emotional stimuli on the Emotional Flexibility task (EST), but it remains unclear if this effect is speci c to social stimuli or extends to all emotional stimuli. Therefore, we developed a new task (referred to as EST-2) that includes both social and non-social emotional stimuli to explore the impact of the social dimension on exibility in autistic and non-autistic individuals.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations